Sistem Manajemen Pemantauan Lapangan Dengan Pemindaian QR Code (Studi Kasus: Rutan Kelas IIB Bintuni) - Fadel Mubarak; Lorna Yertas Baisa; Andreas Leonardo Sumendap (Universitas Islam Raden Rahmat, Malang, 2024)
This study aims to develop a field monitoring management system with QR Code scanning at Bintuni Class IIB Penitentiary. Previous conventional methods have problems in data accuracy and efficiency. This system is expected to improve accuracy, efficiency, and security. The research methods include problem identification, analysis, design, development, and testing. The results of the study indicate that the system is able to automate monitoring, reduce manual errors, and accelerate data collection. The trial using Black Box Testing by three experts showed good results, and the System Usability Scale test got a score with an average value of 82.5, indicating that the system is feasible and according to user needs. The implementation of this system is effective and reliable to improve the quality of management and security at Bintuni Class IIB Penitentiary.